A4.23 S100 proteins induce canonical WNT signalling, which causes increased expression of MMPS in the synovium. (13th February 2015) - van den Bosch, MH; Blom, AB; Hoek, RP; Schelbergen, RF; Suen, SW; van Erp, AE; van den Berg, WB; van der Kraan, PM; van Lent, PL
Abstract : Background/Objectives: Many osteoarthritis (OA) patients show synovial activation, which is thought to be involved in joint destruction. Previously, we found that the alarmins S100A8/A9 and members of the Wnt signalling pathway were increased in the joints during experimental OA. S100A9KO mice showed reduced pathology in experimental OA. Canonical Wnt signalling has been linked to OA, but the role of the synovium in OA under the influence of Wnt signalling is unclear. In this study we investigated whether S100 proteins induce Wnt signalling and whether induction of Wnt signalling led to increased synovial expression of MMPs. Methods: Pathway analysis of microarray data from synovium of a collagenase-induced OA was done using DAVID. Activation of Wnt signalling was determined with β-catenin immunostaining. Gene expression was analysed by qPCR. Human OA synovial tissue collected from joint replacement surgery and stimulated with members of the Wnt signalling pathway or blocked with the Wnt inhibitors FrzB and DKK-1. Results: Pathway analysis showed enrichment of Wnt signalling in the synovium during experimental OA. Because upregulation of both S100 and Wnt proteins during experimental OA showed comparable kinetics, we determined if S100 proteins could induce Wnt signalling. We found that injections of S100A8 into mouse knee joints led to increased Wnt16 and WISP1 expression in the synovium and β-catenin accumulation in the joint. Underlining an interrelationship between Wnt signalling and S100A8/9, we found less β-catenin accumulation during experimental OA in S100A9KO mice. To determine the effects of canonical Wnt signalling in the synovium, we overexpressed Wnt8a and 16 in the synovium with adenoviral vectors, which resulted in increased MMP expression in the synovium. To translate this finding to a human situation, we stimulated human OA synovial tissues with Wnt3a, as a model for a canonical Wnt. This led to significantly increased expression of MMP1, MMP9 and MMP13. Next, we hypothesised that if Wnt signalling was increased in OA synovium, we should be able to decrease the expression of MMPs by blocking the Wnt signalling pathway. Inhibition of Wnt signalling by both FrzB, a general Wnt inhibitor, and DKK-1, selectively blocking canonical Wnt signalling, led to significantly decreased expression of various MMPs. Conclusions: S100 proteins are able to increase Wnt signalling. Stimulation of human OA synovium with Wnts and WISP1 increases the expression of MMPs, whereas blocking Wnt signalling results in decreased expression of MMPs. This underlines synovial Wnt expression to be a potential target for OA therapy.